2017
DOI: 10.3389/fmars.2017.00311
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Experimental Acidification and Eutrophication on Reef Sponge Bioerosion Rates

Abstract: Health of tropical coral reefs depends largely on the balance between constructive (calcification and cementation) and destructive forces (mechanical-chemical degradation). Gradual increase in dissolved CO 2 and the resulting decrease in carbonate ion concentration ("ocean acidification") in ocean surface water may tip the balance toward net mass loss for many reefs. Enhanced nutrients and organic loading in surface waters ("eutrophication"), may increase the susceptibility of coral reef and near shore enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 64 publications
8
49
1
Order By: Relevance
“…To date, only one controlled laboratory study, focused on the Caribbean excavating sponge Cliona caribbae, has experimentally tested the impacts of nutrient pollution on bioerosion. The authors manipulated labile DOC for one week which subsequently drove increases in NH þ 4 and PO 32 4 , but kept NO 2 3 þ NO 2 2 stable: chemical bioerosion rates, but not total bioerosion (quantified as a change in buoyant weight), increased in their eutrophic treatments relative to controls [62]. Our study used different methods to manipulate nutrients, had a longer exposure time and also focused on a multi-species assemblage (coral rubble).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one controlled laboratory study, focused on the Caribbean excavating sponge Cliona caribbae, has experimentally tested the impacts of nutrient pollution on bioerosion. The authors manipulated labile DOC for one week which subsequently drove increases in NH þ 4 and PO 32 4 , but kept NO 2 3 þ NO 2 2 stable: chemical bioerosion rates, but not total bioerosion (quantified as a change in buoyant weight), increased in their eutrophic treatments relative to controls [62]. Our study used different methods to manipulate nutrients, had a longer exposure time and also focused on a multi-species assemblage (coral rubble).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, all particulate material produced during the entire duration of the incubation (~1 h) was collected as a measure for mechanically removed substratum (mechanical erosion). Chemical and mechanical erosion of sponge infested and control cores was determined at day and night in the FT incubation because erosion rates of sponges, particularly symbiont-bearing species, were found to be affected by light availability (diurnal variation) [ 34 , 64 , 65 ]. Flow through incubations were run for all six sponge species.…”
Section: Methodsmentioning
confidence: 99%
“…This technique has now been widely adopted to quantify effects of environmental change and future climate scenarios on rates of bioerosion (e.g. [ 34 , 35 , 47 , 48 , 49 ]). A major disadvantage of this method, however, is that sponges are kept in a limited body of water for a relatively long time, which could strongly affect the metabolism of the sponge following food and oxygen depletion and the accumulation of waste products [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the integrated effects due to organismal interactions cannot be assessed with such an approach. For example, ocean acidification may reduce coral NCC (Andersson et al, 2012) and at the same time increase erosion rates by sponges (Fang et al, 2013;Webb et al 2017). Census approach has yet to include the role of several bioeroders (excavating sponges) (Murphy et al, 2016), which have been observed to become increasingly dominant on Caribbean reefs (Chaves-Fonnegra, Zea and Gómez, 2007).…”
Section: Introductionmentioning
confidence: 99%